HUBUNGAN ANTARA HARGA DAN KUALITAS LAYANAN DENGAN KEPUASAN PELANGGAN BLACKBERRY TELKOMSEL - Nuria Anindita Putri (Perpustakaan Universitas Surabaya, 2013)
The purpose of this research is to examine the correlation between price and service quality with customer satisfaction. The results showed there is correlation between price and quality service with customer satisfaction Blackberry Telkomsel (R=0.563, p=0.000), correlation between price and customer satisfaction Blackberry Telkomsel (r = 0263, p = 0.000), and correlation between the quality of service with Blackberry Telkomsel customer satisfaction (r = 0.441, p = 0.000). Furthermore, compared with the price, quality of service has a greater influence on customer satisfaction.